2017
DOI: 10.1515/mper-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risk Management Practices on IT Project Success

Abstract: Successful management of an information technology (IT) project is the most desirable for all organisations and stakeholders. Many researchers elaborated that risk management is a key part of project management for any project size. Risk management is so critical because it provides project managers with a forward-looking view of both threats and opportunities to improve the project success. The objectives of this research are to explore organisational factors affecting IT project success and risk management p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
0
25
2
5
Order By: Relevance
“…The findings failed to concur with reference [27] who contradicts the findings by indicating that most SMEs project failed to assess risk measures leading to poor construction SMEs project performance in terms of timeliness, profitability, costs and project schedules. Another study contradicting the current findings is that of reference [39] although it was indicated that all risk management practices namely; risk identification, risk assessment, risk response planning, and risk monitoring and control are required for project performance and project success, it was statistically established that there is an insignificant relationship between risk assessment and project success, suggesting that risk assessment negatively influences project success. This result indicates that risk analysis practices should be limited to avoid a negative impact on project scheduled time and budget.…”
Section: Results From Efacontrasting
confidence: 87%
“…The findings failed to concur with reference [27] who contradicts the findings by indicating that most SMEs project failed to assess risk measures leading to poor construction SMEs project performance in terms of timeliness, profitability, costs and project schedules. Another study contradicting the current findings is that of reference [39] although it was indicated that all risk management practices namely; risk identification, risk assessment, risk response planning, and risk monitoring and control are required for project performance and project success, it was statistically established that there is an insignificant relationship between risk assessment and project success, suggesting that risk assessment negatively influences project success. This result indicates that risk analysis practices should be limited to avoid a negative impact on project scheduled time and budget.…”
Section: Results From Efacontrasting
confidence: 87%
“…Previous researches have been investigated the effect of system and information quality on user satisfaction and project achievement. They found that that system and information quality had a significant effect on user satisfaction and project achievement [15] [16].…”
Section: Figure 1 the Progress Of Infrastructure In Indonesiamentioning
confidence: 99%
“…Given the current uncertainty and the last global economic crisis of 2008, risk management has gained more importance and has revealed the deficiency of its application at both organizational and project levels Mikes and Kaplan, 2013;Pimchangthong and Boonjing, 2017). Organizations such as the Project Management Institute (PMI), the International Organization for Standardization (ISO), and the Australia's Standard Organization as well as academics, professionals, experts, governments, etc.…”
Section: Risk Managementmentioning
confidence: 99%